Entrepreneurial capability (EC) environment in ASEAN-05 emerging economies: An empirical approach - Munshi Naser Ibne Afzal; Kasim Mansur (Emerald Publishing Limited, 2018)
Purpose – The entrepreneurial capability (EC) environment refers to the general social and economic settings of a given local/regional entrepreneurship environment. The primary purpose of this study is to uncover key indicators of the EC milieu and test these components empirically within the context of the Association of South East Asian Nations (ASEAN)-5 economies to elucidate the current state of their EC environments, at the regional and national levels. To this end, the aim of this study is twofold. First, this work endeavors to explicate the determinants of EC, with aims of elucidating its association to commercial opportunities in (ASEAN)-5 economies, namely, Indonesia, Malaysia, the Philippines, Singapore and Thailand. Next, this study applies the developed theory, including the identified determinants of EC to empirically test the efficiency and imperative coefficients of variables that have an impact on perceived entrepreneurial capabilities within a given environment. Design/methodology/approach – This research applies two frontier models, namely, the consistent estimation of fixed-effects and linear transformation stochastic frontier models, to assess the coefficients of significant EC variables for the panel sample. Data corresponding to the assessed variables were retrieved from the databases of the Global Entrepreneurship Monitor (GEM) – 2016 and the World Competitiveness Yearbook (WCY) – 2016, for the period, 2010-2016. Findings – The attained results suggest that factors corresponding to the variables “Entrepreneurship as a good career choice” and “perceived opportunities” have played a significantly positive role on the EC environment of ASEAN 05, although findings suggest both factors may still be improved upon. Conversely, the “fear of failure rate” factor was shown to have exerted a negative impact on the efficiency of the EC environment of ASEAN 05. Other important variables – such as intellectual property rights, university education and knowledge transfer rate – were shown to generate a positive impact on the EC environment of these economies. Originality/value – This study makes an important contribution to the entrepreneurship literature and can stimulate policymakers to rethink the EC settings of ASEAN-05 in their pursuit of an innovation-driven region.